Frontiers of research in economic theory the Nancy L. Schwartz Memorial Lectures, 1983-1997 - Schwartz, Nancy Lou; Jacobs, Donald P.; Kalai, Ehud 1942-; Kamien, Morton I. (Econometric Society monographs, 1998)
'Leading economists presenting fundamentally important issues in economic theory' is the theme of the Nancy Schwartz lectures series held annually at the J. L. Kellogg Graduate School of Management of Northwestern University. Reporting on lectures delivered in the years 1983 through 1997, this collection of essays discusses economic behavior at the individual and group level and the implications to the performance of economic systems. Using non-technical language, the speakers present theoretical, experimental, and empirical analysis of decision making under uncertainty and under full and bounded rationality, the influence of economic incentives and habits, and the effects of learning and evolution on dynamic choice. Perfect competition, economic development, social insurance and social mobility, and negotiation and economic survival, are major economic subjects analyzed through our understanding of economic behavior